Diagnostic guide enabling distinction between taphonomic stains and enamel hypomineralisation in an archaeological context. (February 2017) - Garot, Elsa; Couture-Veschambre, Christine; Manton, David; Rodriguez, Vincent; Lefrais, Yannick; Rouas, Patrick
Highlights: Enamel stained by post-mortem processes may have a similar appearance to MIH. Our diagnostic guide enables to identify developmental hypomineralisation of enamel to taphonomic discolorations. Hypomineralised enamel has higher phosphate/β-carbonate ratio and lower mineral density. Taphonomic discolorations are highlighted using X-ray fluorescence analyses. Abstract: Objective: Molar Incisor Hypomineralisation (MIH) is a structural anomaly that affects the quality of tooth enamel and has important consequences for oral health. The developmentally hypomineralised enamel has normal thickness and can range in colour from white to yellow or brown with or without surface breakdown. The possibility of finding MIH in 'ancient populations' could downplay several current aetiological hypotheses (e.g., dioxin derivatives, bisphenols, antibiotics) without excluding the possible multifactorial aspect of the anomaly. In an archaeological context, chemical elements contained in the burial ground can stain teeth yellow or brown and therefore might create a taphonomic bias. The purpose of the present study is to test a proposed diagnostic guide enabling determination of the pathological or taphonomic cause of enamel discolouration and defects that resemble MIH present on 'ancient teeth'. Design: Two sample groups including MIH discoloration (n = 12 teeth) from living patients, taphonomic discoloration (n = 9 teeth) and unknown discoloration (n = 2 teeth) from medieval specimens were tested. Three non-destructive methods—Raman spectroscopy, X-ray micro-computed tomography and X-ray fluorescence were utilised. Results: Hypomineralised enamel has decreased mineral density (p < 0.0001) and increased phosphate/β-carbonate ratio (p < 0.01) compared to normal enamel whereas relative concentrations of manganese, copper, iron and lead are similar. In taphonomic discoloration, relative concentrations of these elements are significantly different (p < 0.05) to normal enamel whereas mineral density and Raman spectra profile are comparable. Conclusions: Enamel hypomineralisation can be distinguished from taphonomic staining in archaeological teeth.